Development of HEK293T-produced recombinant receptor-Fc proteins as potential candidates against canine distemper virus - Song, Lingling; Shan, Hu; Huang, Juan (Frontiers in Veterinary Science, 2023)
Canine distemper (CD) is a highly contagious viral disease in worldwide. Although live attenuated vaccine is available as a preventive measure against the disease, cases of vaccination failure highlight the importance of potential alternative agent against canine distemper virus (CDV). CDV infects cells mainly by binding SLAM and Nectin-4 receptor. Here, to develop a new and safe antiviral biological agent for CD, we constructed and expressed CDV receptor proteins fused with Fc region of canine IgG-B, namely, SLAM-Fc, Nectin-Fc and SLAM-Nectin-Fc in HEK293T cells. The receptor-Fc proteins efficiently bound to receptor binding domain (RBD) of CDV-H, meanwhile, these receptor-Fc proteins competitively inhibited the binding of His-tagged receptor proteins (SLAM-His or Nectin-His) to CDV-H-RBD-Flag protein. Importantly, receptor-Fc proteins exhibited potent anti-CDV activity in vitro. Treatment with receptor-Fc proteins at the pre-entry stage dramatically suppressed CDV infectivity in Vero cells. The minimum effective concentration (MEC) of SLAM-Fc, Nectin-Fc and SLAM-Nectin-Fc was 0.2 μg/mL, 0.2 μg/mL, 0.02 μg/mL. The 50% inhibition concentration (IC50) of three proteins was 0.58 μg/mL, 0.32 μg/mL and 0.18 μg/mL, respectively. Moreover, treatment with receptor-Fc proteins post viral infection can also inhibit CDV reproduction, the MEC of SLAM-Fc, Nectin-Fc and SLAM-Nectin-Fc was same as pre-treatment, and the IC50 of receptor-Fc proteins was 1.10 μg/mL, 0.99 μg/mL and 0.32 μg/mL, respectively. The results suggested that the receptor-Fc proteins were more effective for pre-entry treatment than post-infection treatment, furthermore, SLAM-Nectin-Fc was more effective than SLAM-Fc and Nectin-Fc. These findings revealed the receptor-Fc proteins were promising candidates as inhibitor against CDV.